Cost-effectiveness of portable-automated ABR for universal neonatal hearing screening in India - Sahoo, Krushna Chandra; Dwivedi, Rinshu; Athe, Ramesh; Chauhan, Akshay; Jain, Shalu; Sahoo, Rakesh Kumar; Bhattacharya, Debdutta; Rajsekhar, Kavitha; Pati, Sanghamitra (Frontiers in Public Health, 2024)
The World Health Organization considers Universal Neonatal Hearing Screening (UNHS) essential to global public health. Rashtriya Bal Swasthya Karyakram has included newborn hearing screening in India since 2013. The program faces human, infrastructure, and equipment shortages. First-line hearing screening with improved diagnostic accuracy is needed. The Portable Automated Auditory Brainstem Responses (P-AABR) can be used in remote areas for UNHS due to its low infrastructure needs and diagnostic accuracy. This study evaluated the cost-effectiveness of P-AABR in UNHS. We employed an analytical model based on decision trees to assess the cost-effectiveness of Otoacoustic Emission (OAE) and P-AABR. The total cost to the health system for P-AABR, regardless of true positive cases, is INR 10,535,915, while OAE costs INR 7,256,198. P-AABR detects 262 cases, whereas OAE detects 26 cases. Portable Automated ABR costs INR 97 per case detection, while OAE costs INR 67. The final ICER was 97407.69. The P-AABR device is cost-effective, safe and feasible for UNHS Rashtriya Bal Swasthya Karyakram (RBSK) programs. Beyond reducing false referrals and parent indirect costs, it detects more hearing-impaired infants. Even in shortages of skilled workers, existing staff can be trained. Thus, this study suggests integrating this device into community and primary health centers to expand UNHS coverage.